Pengaruh Minyak Hewani dan Nabati yang Diberikan pada Wadah Pemeliharaan untuk Meningkatkan Kelangsungan Hidup Larva Ikan Kakap Putih (Lates calcarifer) - Elbiansyah Putra Elbiansyah; Tri Yulianto; Shavika Miranti (Intek Akuakultur, 2021)
This research was held at BBI Pengujan for 10 day.The purpose of this research was to determined the effect of different oil addition on water surface and the best oil typef or barramundi larval survival rate. the experiment design was Completely Randomized Design (CRD) with 4 treatment and 3 replication; without oil addition (A); 0,3 ml/m2 of squid oil (B); 0,3 ml/m2 coconut oil (C) and 0,3 ml/m2 at palm oil (D). The datas was obtained with One-Way ANOVA. The best resolt was treatmen with addition 0,3 ml/m2 at coconut oil (C), the survival rate was 27,87 %, absolute and while for the abnormality was not different significant for all treatment. The lowest abnormality was B treatment with 1,36%.